ECONOMISTAS E POLÍTICA NO BRASIL: A PARTICIPAÇÃO DOS ECONOMISTAS NO PODER NOS GOVERNOS FHC (1995-2002) E LULA (2003-2010) - José Carlos Martines Belieiro Junior (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
The main goal of this work is to discuss the participation of economists in the FHC and Lula governments, as well as making some notes on the relationship between economic management and democracy in contemporary Brazil. The perspective is the analyse of political analysis of economic policy in the 90s and 2000. The article makes references to the 1980s, citing the Cruzado Plan in the in the learning process for the success of economic stabilization, which occurred in 1994. The analysis of reference is the relationship between economic management and authoritarian tradition and centralizing post-1930 Brazilian state, seeking to update this debate, from the years 1990 and 2000, from the perspective of two different democratic governments. The article focuses attention on decision-makers, economists, but looking ready known elements for the identification of groups such as the academic and political movement. The main hypothesis is that the authoritarian and centralist tradition remained in the democratic period due to the need to combat the inertial inflation. On the other hand, the democratic regime has been able to change logic and patterns of state and society relationship and the relationship between politics and economic policy in Brazil.